The Shehata technique for undescended testes that cannot be brought into the scrotum in one operation—a case series and meta-analysis - Lin, Zhenying; Yu, Zhongjing; Li, Huanyuan; Wu ri ni, Letu; Zhang, Baoxin (Frontiers in Pediatrics, 2024)
Background Fowler–Stephens orchiopexy is commonly used for testes that cannot be brought into the scrotum in one operation. However, this surgical technique may result in a higher rate of testicular atrophy postoperatively. Methods During the period between 2019 and 2023, we analyzed the cases of 20 patients in whom the Shehata technique was applied for testes that could not be brought into the scrotum in one operation, and we conducted a meta-analysis to explore the incidence of testicular atrophy vis-à-vis the Shehata technique and Fowler–Stephens orchiopexy. Results The average age of the 20 patients was 3.78 (0.76–11.42) years. The blood supply to the testes was satisfactory, with the absence of atrophy, and the testes could be brought into the scrotum in stage II surgery. A postoperative reexamination with ultrasound revealed that the testes were securely positioned within the scrotum, with good blood supply and no atrophy, which was in contrast to their condition before the operation. The volume of the testes postoperatively was significantly greater than that of the preoperative testes (p = 0.009). There were no statistically significant differences in the growth rate of volume of the testes between the surgically treated side and the contralateral side (p = 0.25). The meta-analysis showed that the Shehata technique resulted in a lower incidence of testicular atrophy compared with Fowler–Stephens orchiopexy (p = 0.01). Conclusions The Shehata technique preserves the main vessels of the testes with a lower incidence of testicular atrophy, which may be a valid and safe alternative to the Fowler–Stephens technique.